Textual Distortion in Hadith Transmission: A Critical Philological Analysis of Tashīf and Taḥrīf in Islamic Manuscript Tradition - Syihabuddin, Muhammad; Masruri, M. Hadi; Qurrata Ayunin, Fikri (Tashwirul Afkar, 2024)
This study aims to investigate the phenomena of tashīf (scribal error) and taḥrīf (textual distortion) in classical Arabic manuscripts, particularly in the transmission of ḥadīth texts, as independent analytical categories within Arabic philology. Motivated by the scarcity of focused studies on these textual deviations, the research highlights their epistemological significance and role in shaping Islamic intellectual tradition. Employing a qualitative-descriptive approach grounded in classical philological sources and contemporary critical theory, this study draws data from primary hadith texts and their commentaries through documentation and content analysis methods. The findings reveal that most errors stem from the visual similarity of Arabic letters and the absence of diacritical marks in early scripts, which often lead to semantic distortions and affect the credibility of transmitters. The study also illustrates the ongoing relevance of tashīf and taḥrīf in both classical and modern contexts, including manuscript editing and theological interpretation. These phenomena have significant implications for preserving textual authenticity, understanding ideological shifts, and developing critical philological methods. The originality of this research lies in its integration of classical Islamic studies with critical philology—particularly Bernard Cerquiglini’s theory of textual variance—offering a novel framework to reexamine the dynamics of textual authority and interpretive pluralism in Islamic scholarship.